History of Adverse Pregnancy Outcomes in Women With Pulmonary Arterial Hypertension: A Single‐Center Pilot Study - Jessica B. Badlam; Renee D. Stapleton; Peter W. Callas; Ira M. Bernstein; Eric D. Austin (Pulmonary Circulation, 2025)
ABSTRACT Single‐center pilot study suggests a threefold increase in self‐reported history of adverse pregnancy outcomes (APO) among women with subsequent diagnosis of pulmonary arterial hypertension (PAH). Females with PAH and a history of APO were younger and had higher mean pulmonary artery pressures at diagnosis compared to those without a history of APO.